1986
DOI: 10.1002/masy.19860060111
|View full text |Cite
|
Sign up to set email alerts
|

Free radical ring‐opening polymerization and its use to make biodegradable polymers and functionally terminated oligomers

Abstract: Abstract-Since a carbon-oxygen double bond i s considerably more s t a b l e a n a carbon-carbon double bond, i t has been possible to use t h i s d r i v i n g force to promote free r a d i c a l ring-opening polymerization o f unsaturated heterocyclic compounds. This process, f o r the f i r s t time, has permitted the i n t r o d u c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The polymerization of the 5-membered CKA monomer (CKA1, Figure 68) clearly showed that the formation of polyester increased with an increase of the temperature (50% of ringopening at 60 °C, 83% at 125 °C, 10 and 100% at 160 °C). 183 This trend was observed with other CKA monomers. 181 It has also been shown that addition of a solvent also facilitated the ring-opening, which was explained by favored intramolecular mechanisms (CKA ring-opening in this case), upon dilution.…”
Section: Radical Polymerizationsupporting
confidence: 67%
See 3 more Smart Citations
“…The polymerization of the 5-membered CKA monomer (CKA1, Figure 68) clearly showed that the formation of polyester increased with an increase of the temperature (50% of ringopening at 60 °C, 83% at 125 °C, 10 and 100% at 160 °C). 183 This trend was observed with other CKA monomers. 181 It has also been shown that addition of a solvent also facilitated the ring-opening, which was explained by favored intramolecular mechanisms (CKA ring-opening in this case), upon dilution.…”
Section: Radical Polymerizationsupporting
confidence: 67%
“…Several studies, and in particular Bailey's work, proved the importance of the temperature to facilitate the ring-opening process. The polymerization of the 5-membered CKA monomer (CKA1, Figure68) clearly showed that the formation of polyester increased with an increase of the temperature (50% of ringopening at 60 °C, 83% at 125 °C, 10 and 100% at 160 °C) 183. This trend was observed with other CKA monomers 181.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…These polymers are therefore degradable upon exposure to an acidic or basic environment or to ultraviolet irradiation. 1,3,7,12,13,16,17 For this reason, CKA and CA polymers are attractive candidates in medical and lithographic applications. 1,12,18 Scheme 2 illustrates the mechanism of radical ringopening polymerization for both the CKA and CA monomers.…”
Section: Introductionmentioning
confidence: 99%